2002
DOI: 10.1098/rstb.2001.1022
|View full text |Cite
|
Sign up to set email alerts
|

Elastic proteins: biological roles and mechanical properties

Abstract: The term 'elastic protein' applies to many structural proteins with diverse functions and mechanical properties so there is room for confusion about its meaning. Elastic implies the property of elasticity, or the ability to deform reversibly without loss of energy; so elastic proteins should have high resilience. Another meaning for elastic is 'stretchy', or the ability to be deformed to large strains with little force. Thus, elastic proteins should have low stiffness. The combination of high resilience, large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
632
2
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 754 publications
(672 citation statements)
references
References 30 publications
15
632
2
3
Order By: Relevance
“…1a). There is strong evidence supporting the hypothesis that elastin is both a highly compliant and a resilient protein (Gosline et al 2002). Gross mechanical testing studies on recombinant elastin membranes and rehydrated bovine nuchal ligaments, which had been subjected to repeated autoclaving to remove associated proteins, demonstrated that even small forces produce large extensions (Aaron and Gosline 1981), whilst stress-strain curves for extensions up to 50% demonstrated the ability of recombinant elastin peptides to recoil elastically (Keeley et al 2002).…”
Section: Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…1a). There is strong evidence supporting the hypothesis that elastin is both a highly compliant and a resilient protein (Gosline et al 2002). Gross mechanical testing studies on recombinant elastin membranes and rehydrated bovine nuchal ligaments, which had been subjected to repeated autoclaving to remove associated proteins, demonstrated that even small forces produce large extensions (Aaron and Gosline 1981), whilst stress-strain curves for extensions up to 50% demonstrated the ability of recombinant elastin peptides to recoil elastically (Keeley et al 2002).…”
Section: Structure and Functionmentioning
confidence: 99%
“…Where a rod of length l 0 and cross-sectional area A is stretched to a length l by a force F, the elastic modulus (E) is calculated from the stress divided by the strain. The value of E relates to the biological function of a macromolecules; the elastic modulus of fibrillar collagen (1,200 MPa), for example, is relatively high reflecting the role of collagen fibrils in resisting tensile forces (Gosline et al 2002), in contrast E for elastin is low (1.1 MPa) (Aaron and Gosline 1981) and a small force will produce a large extension. The elastic modulus of fibrillin microfibrils, however, remains controversial with estimates ranging from 1.0 MPa (Aaron and Gosline 1981) to 96 MPa (Sherratt et al 2003) Gallagher et al 2005;Hubmacher et al 2006;Kielty et al 2002).…”
Section: Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incudostapedial joint-capsule ligament has been found to consist mainly of elastin (Davies 1948;Harty 1953), rather than collagen as found in most joint capsules. The Young's modulus of elastin fibers from bovine ligament has been reported as 1.1 MPa (e.g., Gosline et al 2002). A value of 1 MPa has been adopted here for the joint capsule.…”
Section: Materials Propertiesmentioning
confidence: 99%